Effect of Methamphetamine Hydrochloride on Pregnancy Outcome: A Systematic Review and Meta-analysis. Issue 3 (May 2018) - Kalaitzopoulos, Dimitrios-Rafail; Chatzistergiou, Konstantinos; Amylidi, Anna-Lea; Kokkinidis, Damianos G.; Goulis, Dimitrios G.
Abstract : Background: Methamphetamine hydrochloride is 1 of the most widespread psycho-stimulants in the world. Nevertheless, its effect on pregnant women and their neonates has not been investigated extensively. Objective: To systematically review the literature for the effect of methamphetamine exposure during pregnancy to neonatal and pregnancy outcomes. Materials and methods: A meta-analysis of retrospective, case-control studies was conducted. Inclusion criteria were women who have used methamphetamine during pregnancy, determined by self-report, maternal or neonatal urine test, and/or meconium toxicology, compared with control women not taking methamphetamine. Main study outcomes were gestational age at birth, neonatal characteristics (birth weight, head circumference, body length), and prevalence of gestational hypertensive disorders. Results: Eight studies involving 626 women taking methamphetamine during pregnancy and 2626 controls were included in the meta-analysis. Pregnancies complicated by the use of methamphetamine resulted in younger gestational age at birth (mean difference [MD] −0.90 weeks, 95% confidence interval [CI] −0.11, −1.69), lower birth weight (MD −245 g, 95% CI −137, −353), head circumference (MD −0.88 cm, 95% CI −0.48, −1.28), body length (MD −0.94 cm, 95% CI −0.55, −1.32), and Apgar score (MD −0.94, 95% CI −0.33, −1.54) compared with control pregnancies. On the contrary, there was no statistical difference on the incidence of pre-eclampsia (risk ratio [RR] 1.77, 95% CI 0.75, 4.14) and hypertensive complications (RR 1.62, 95% CI 0.37, 7.06). Conclusions: Use of methamphetamine during pregnancy results in a deterioration of neonatal somatometric characteristics (birth weight, head circumference, body length), but not in excessive pregnancy complications (hypertension). Abstract : Supplemental Digital Content is available in the text